2022
DOI: 10.2196/21313
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Accidents or Chronic Disorders From Improper Use of Mobile Phones: A Systematic Review and Meta-analysis

Abstract: Background Mobile phone use has brought convenience, but the long or improper use of mobile phones can cause harm to the human body. Objective We aimed to assess the impact of improper mobile phone use on the risks of accidents and chronic disorders. Methods We systematically searched in PubMed, EMBASE, Cochrane, and Web of Science databases for studies published prior to April 5, 2019; relevant reviews were… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 100 publications
(105 reference statements)
0
8
0
Order By: Relevance
“…Cho et al ( 33 ) found that mobile phone call duration was significantly associated with the severity of headaches. A recent meta-analysis in human studies ( 34 ) also showed that increasing mobile phone use was associated with a higher risk of DNA damage. Due to the observed detrimental effects of calling time and RF-EMF radiation on a range of health outcomes in humans among the above studies ( 31 34 ), we speculate that RF-EMF radiation of mobile phones may also play a role in the development of CKD.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Cho et al ( 33 ) found that mobile phone call duration was significantly associated with the severity of headaches. A recent meta-analysis in human studies ( 34 ) also showed that increasing mobile phone use was associated with a higher risk of DNA damage. Due to the observed detrimental effects of calling time and RF-EMF radiation on a range of health outcomes in humans among the above studies ( 31 34 ), we speculate that RF-EMF radiation of mobile phones may also play a role in the development of CKD.…”
Section: Discussionmentioning
confidence: 97%
“…A recent meta-analysis in human studies ( 34 ) also showed that increasing mobile phone use was associated with a higher risk of DNA damage. Due to the observed detrimental effects of calling time and RF-EMF radiation on a range of health outcomes in humans among the above studies ( 31 34 ), we speculate that RF-EMF radiation of mobile phones may also play a role in the development of CKD. Nevertheless, a previous cohort study in Denmark found that there were no significant associations between mobile phone use and tumor risks ( 35 38 ), except for a significant increase in the risk of smoking-related cancers in women and a significant decrease in the risks of smoking-related cancers in men ( 38 ).…”
Section: Discussionmentioning
confidence: 97%
“… 33 also found a similar inverse association between daily talking time on the cell phone and the sperm concentration. A recent meta-analysis in human studies 34 further showed that increased mobile phone use was related to an increased risk of DNA damage. Since the observed harmful effects of calling time and RF-EMF radiation on different health outcomes, 32–34 we speculate that relatively long-term exposure to RF-EMF during making or receiving calls may possibly also have an important role in the occurrence of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…This study further intends to analyze how the potential health risks, especially eye health, in smartphone use among children in urban and rural areas. The results showed that there was no difference in potential eye health risks in smartphone use between urban and rural children [11,[13][14][15][16]. Some Children's behaviors in using smartphones have a risk of health problems including eye health.…”
Section: Discussionmentioning
confidence: 99%